Natural killer cells occupy unique spatial neighborhoods in HER2- and HER2+ human breast cancers - Femke A. I. Ehlers; Katie E. Blise; Courtney B. Betts; Shamilene Sivagnanam; Loes F. S. Kooreman; E. Shelley Hwang; Gerard M. J. Bos; Lotte Wieten; Lisa M. Coussens (Breast Cancer Research)
Abstract Tumor-infiltrating lymphocytes are considered clinically beneficial in breast cancer, but the significance of natural killer (NK) cells is less well characterized. As increasing evidence has demonstrated that the spatial organization of immune cells in tumor microenvironments is a significant parameter for impacting disease progression as well as therapeutic responses, an improved understanding of tumor-infiltrating NK cells and their location within tumor contextures is needed to improve the design of effective NK cell-based therapies. In this study, we developed a multiplex immunohistochemistry (mIHC) antibody panel designed to quantitatively interrogate leukocyte lineages, focusing on NK cells and their phenotypes, in two independent breast cancer patient cohorts (n = 26 and n = 30). Owing to the clinical evidence supporting a significant role for NK cells in HER2+ breast cancer in mediating responses to Trastuzumab, we further evaluated HER2- and HER2+ specimens separately. Consistent with literature, we found that CD3+ T cells were the dominant leukocyte subset across breast cancer specimens. In comparison, NK cells, identified by CD56 or NKp46 expression, were scarce in all specimens with low granzyme B expression indicating reduced cytotoxic functionality. Whereas NK cell density and phenotype did not appear to be influenced by HER2 status, spatial analysis revealed distinct NK cells phenotypes regarding their proximity to neoplastic tumor cells that associated with HER2 status. Spatial cellular neighborhood analysis revealed multiple unique neighborhood compositions surrounding NK cells, where NK cells from HER2- tumors were more frequently found proximal to neoplastic tumor cells, whereas NK cells from HER2+ tumors were instead more frequently found proximal to CD3+ T cells. This study establishes the utility of quantitative mIHC to evaluate NK cells at the single-cell spatial proteomics level and illustrates how spatial characteristics of NK cell neighborhoods vary within the context of HER2- and HER2+ breast cancers.